Apollonius Rhodius 1.103: A Discussion of a New Emendation. Issue 1 (1st January 2021) - Bär, Silvio
Abstract : In Apoll. Rhod. Arg. 1.103, there are three textual variants for the adjective that accompanies the noun ὁδόν: κοινήν, κϵινήν and κϵίνην. Recently, the emendation σκοτίην has been suggested; a suggestion that is seemingly supported by a parallel in Arg. Orph. 41. It is argued here that this emendation is unwarranted and that probably either κϵινήν or κϵίνην is authentic, whereby the two variants constitute wordplay that reinforces the ironic underlayer of the context. Further, it is demonstrated that Arg. Orph. 41 does not provide a convincing parallel and that it thus does not support the suggested emendation.